Barium titanate / gold / cadmium sulfide heterojunction photocatalyst and preparation and application thereof
Patent Information
- Application Number
- CN202611392465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]针对现有技术中所存在的钛酸钡/硫化镉异质结界面接触不紧密、界面电荷传输阻力高,导致光生载流子分离与传输效率不足、光催化析氢性能受限的技术问题,本发明提供一种钛酸钡/金/硫化镉异质结光催化剂及其制备方法和应用
[0029]本发明将金纳米颗粒负载于钛酸钡基底表面,并使硫化镉材料同时与金纳米颗粒和钛酸钡基底接触,使金纳米颗粒位于钛酸钡基底与硫化镉材料之间作为电子传输介质,由于金具有高导电性,该结构能够降低界面电荷传输电阻,促进光生载流子从硫化镉侧向钛酸钡侧的跨界面传输,部分界面区域可形成肖特基接触,有望抑制光生电子逆向回流,实现光生电子-空穴空间分离,提升光催化析氢性能。本发明通过“先吸附镉离子、后滴加硫离子”的化学沉淀顺序,使硫化镉优先在金纳米颗粒表面成核生长,得益于Au-S之间的强亲和力,使硫化镉层通过Au-S键锚定于金纳米颗粒表面,增强了异质结界面的接触紧密性,实验表明该制备顺序使硫化镉前驱体沉积顺序对析氢性能影响甚微,而未经金修饰的钛酸钡/硫化镉异质结在优先吸附硫离子时活性急剧下降至优先吸附镉离子时的10%,证明金修饰有效稳定了界面结构;在模拟太阳光照射下(以0.25 M亚硫酸钠和0.35 M硫化钠为牺牲剂),本发明光催化剂的析氢速率达到9.97 mmol·g-1·h-1,分别为钛酸钡/硫化镉异质结(5.23 mmol·g-1·h-1)和原始硫化镉(0.95 mmol·g-1·h-1)的1.9倍和10.5倍;在可见光照射下(λ≥420 nm)析氢性能亦得到显著增强,且该光催化剂在五次连续循环测试中析氢性能基本保持稳定;此外,金纳米颗粒的引入使吸收边发生红移,增强了光捕获能力和可见光利用效率,紫外-可见漫反射光谱显示与钛酸钡/硫化镉异质结相比,本发明的光催化剂在可见光区的吸收强度明显提高。
Smart Images

Figure CN122974338A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalytic materials technology, and relates to heterojunction photocatalysts, particularly to a barium titanate / gold / cadmium sulfide heterojunction photocatalyst, its preparation method, and its application. Background Technology
[0002] Photocatalytic water splitting for hydrogen production utilizes semiconductor materials to convert solar energy into hydrogen energy, representing a crucial approach to addressing energy and environmental challenges. Barium titanate (BaTiO3, BTO) is a typical perovskite ferroelectric material with advantages such as good chemical stability and no pollution; however, it has a wide bandgap (approximately 3.2 eV), a narrow light response range, and poor light capture ability. Cadmium sulfide (CdS), on the other hand, has a narrow bandgap (approximately 2.2 eV) and good visible light response, but its photogenerated carriers recombine easily, and it suffers from photocorrosion. Constructing a type II heterojunction by combining barium titanate and cadmium sulfide allows for the establishment of a built-in electric field through interfacial band matching and work function differences, achieving spatial separation of photogenerated carriers to a certain extent and thus improving the photocatalytic performance of a single component.
[0003] Existing technology CN107670672A discloses a barium titanate-cadmium sulfide composite nanocomposite photocatalyst and its preparation method. Barium titanate is synthesized via a sol-gel method, followed by a stepwise synthesis of the BaTiO3-CdS nanocomposite structure using a co-precipitation method, which improves photocatalytic performance to some extent. However, this binary heterojunction system lacks a metal mediator, hindering the regulation of charge-directed transport and suppression of electron backflow. The high interfacial charge transport resistance limits the interfacial charge transport efficiency, resulting in insufficient separation and transport efficiency of photogenerated carriers, thus restricting further improvement of the heterojunction's photocatalytic hydrogen evolution performance.
[0004] Utilizing the high electrical conductivity of metallic materials as charge transport bridges in heterojunctions can promote interfacial charge migration. Previous studies have introduced Au into the BaTiO3 / g-C3N4 system to construct all-solid-state Z-type heterojunctions, or loaded Au onto the TiO2-CdS interface as an electron transport medium. However, existing BTO / CdS binary heterojunctions do not provide methods for directional charge transport and electron backflow suppression regulated by the metal mediator. Current research lacks systematic exploration of the interfacial characteristics between the metal mediator and the two semiconductors and their regulatory effect on charge transport, especially regarding whether metal nanoparticles can simultaneously form Schottky contacts with both semiconductors, and the synergistic suppression mechanism of the double Schottky barrier on photogenerated electron backflow, which is not fully disclosed in existing technologies. Furthermore, how to precisely position Au at the interface of the two semiconductors, rather than simply loading it onto the surface, to enable it to simultaneously perform the dual functions of reducing interfacial charge transport resistance and suppressing electron backflow, remains a pressing technical challenge in this field. Summary of the Invention
[0005] To address the technical problems in existing technologies, such as poor interfacial contact and high interfacial charge transport resistance in barium titanate / cadmium sulfide heterojunctions, which lead to insufficient separation and transport efficiency of photogenerated carriers and limited photocatalytic hydrogen evolution performance, this invention provides a barium titanate / gold / cadmium sulfide heterojunction photocatalyst, its preparation method, and its application.
[0006] Technical solution
[0007] A barium titanate / gold / cadmium sulfide heterojunction photocatalyst includes a perovskite-phase barium titanate substrate, gold nanoparticles supported on the surface of the barium titanate substrate, and a cadmium sulfide nanoparticle layer. The cadmium sulfide nanoparticle layer at least partially covers the surface of the gold nanoparticles and forms a three-phase contact interface with the gold nanoparticles and the barium titanate substrate in at least a partial region. The gold nanoparticles are located between the barium titanate substrate and the cadmium sulfide nanoparticle layer, serving as an electron transport medium between the barium titanate substrate and the cadmium sulfide nanoparticle layer.
[0008] Furthermore, Schottky contacts are formed between the gold nanoparticles and the barium titanate substrate, and between the gold nanoparticles and the cadmium sulfide nanoparticle layer, respectively, constituting a double Schottky barrier structure.
[0009] This invention reduces the interfacial charge transport resistance by placing gold nanoparticles at the interface region of two semiconductors; the gold nanoparticles can form Schottky contacts with the semiconductors on both sides, suppressing the reverse flow of photogenerated electrons, realizing spatial separation of photogenerated carriers, and improving the photocatalytic hydrogen evolution performance.
[0010] In a preferred embodiment of the present invention, the barium titanate substrate is a perovskite phase barium titanate, whose X-ray diffraction characteristic peaks match those of the standard card PDF#04-007-9931.
[0011] In a preferred embodiment of the present invention, the cadmium sulfide material is a cadmium sulfide nanoparticle layer, which at least partially covers the surface of the gold nanoparticles and is connected to the barium titanate substrate through the gold nanoparticles; at the same time, the cadmium sulfide material also covers at least a portion of the barium titanate substrate that is not loaded with gold nanoparticles and is in direct contact with the barium titanate substrate.
[0012] In a preferred embodiment of the present invention, the average particle size of the gold nanoparticles is 3-7 nm, preferably 5 nm; the actual mass loading of the gold nanoparticles is 0.2-3.5%, preferably 1.6-1.8%. The "actual mass loading" refers to the proportion of the mass of gold element determined by energy-dispersive X-ray spectroscopy (EDS) to the total mass of the barium titanate / gold / cadmium sulfide heterojunction photocatalyst.
[0013] In a preferred embodiment of the present invention, the mass ratio of cadmium sulfide to barium titanate substrate in the cadmium sulfide material is 0.05~0.3:1, preferably 0.062:1.
[0014] A second objective of this invention is to disclose a method for preparing the aforementioned barium titanate / gold / cadmium sulfide heterojunction photocatalyst, comprising:
[0015] S1. Preparation of barium titanate substrate;
[0016] S2. Deposition of gold nanoparticles on barium titanate substrate: The barium titanate substrate is dispersed in water, tetrachloroauric acid solution and ammonia are added, and the reaction is carried out at 70-90 °C for 0.5-2 h. The gold precursor is deposited on the surface of barium titanate substrate by deposition-precipitation method. After centrifugation, washing and drying, the substrate is heat-treated at 300-500 °C for 1-3 h in an inert atmosphere to reduce the gold precursor to metallic gold nanoparticles, thus obtaining barium titanate / gold composite.
[0017] S3. A cadmium sulfide layer is deposited on the surface of a barium titanate / gold composite by chemical precipitation to obtain a barium titanate / gold / cadmium sulfide heterojunction photocatalyst. In this process, the barium titanate / gold composite is first dispersed in a precursor solution containing cadmium ions, so that the cadmium ions are adsorbed on the surface of the barium titanate / gold composite, and then a precursor solution containing sulfur ions is added to carry out the reaction.
[0018] In a preferred embodiment of the present invention, in step S1, when preparing the barium titanate substrate, barium hydroxide octahydrate and tetrabutyl titanate are dispersed in a mixed solvent of water and ethanol at a molar ratio of 1.2 to 2:1, ammonia is added, and the mixture is subjected to a hydrothermal reaction at 180 to 220 °C for 18 to 30 h to obtain the barium titanate substrate.
[0019] In a preferred embodiment of the present invention, in step S2, the amount of tetrachloroauric acid added is calculated based on the theoretical mass loading of gold of 0.5% to 5%. The actual loading can be controlled by adjusting the amount of tetrachloroauric acid added, the reaction temperature, and the reaction time. For example, under a fixed reaction temperature of 80 °C and a reaction time of 1 h, 0.5 mL, 1 mL, 2 mL, 3 mL, 4 mL, and 6 mL of 5 mg / mL HAuCl4 solution are added respectively, and then treated at 300–500 °C for 1–3 h in an inert atmosphere to obtain barium titanate / gold composites with actual loadings of approximately 0.2%–0.3%, 0.5%–0.7%, 1.0%–1.2%, 1.6%–1.8%, 2.1%–2.4%, and 3.0%–3.5%. The specific actual loading is determined by EDS elemental analysis.
[0020] In a preferred embodiment of the present invention, in step S3, when depositing cadmium sulfide material on the surface of the barium titanate / gold composite, the barium titanate / gold composite is dispersed in water, a cadmium acetate dihydrate solution is added, and the mixture is stirred and adsorbed for 20–60 min. Then, a sodium sulfide solution is added and reacted for another 20–60 min, forming cadmium sulfide material through chemical precipitation. The molar ratio of cadmium acetate dihydrate to sodium sulfide is 1:1. The cadmium ion adsorption process is preferably carried out under light-protected conditions to avoid unintended photochemical reactions of the cadmium sulfide precursor under light irradiation, which could affect the selective deposition and interfacial bonding of cadmium sulfide on the surface of gold nanoparticles.
[0021] The present invention also provides the application of the above-mentioned barium titanate / gold / cadmium sulfide heterojunction photocatalyst in photocatalytic water splitting for hydrogen production.
[0022] In a preferred embodiment of the present invention, the photocatalytic water splitting to produce hydrogen is carried out in an aqueous solution containing a sacrificial agent, namely sodium sulfite and sodium sulfide; the photocatalytic water splitting to produce hydrogen is carried out under simulated sunlight or visible light irradiation.
[0023] Furthermore, photocatalytic water splitting for hydrogen production can also be carried out in a pure water system without sacrificial agents, by applying an external electric field or by supplementing it with pyroelectric / piezoelectric effects to drive the entire water splitting process.
[0024] Photoelectric performance testing: The photoelectrochemical performance of the three-electrode system was tested using a CHI-660 electrochemical workstation. A working electrode suitable for photocurrent response and electrochemical impedance spectroscopy (EIS) analysis was prepared. The specific procedure was as follows: 2 mg of sample was placed in a small sample tube, and 200 μL of ethanol and 5 μL of Nafion reagent were added. After ultrasonic dispersion for 1 hour, the sample suspension was carefully and evenly coated onto the FTO conductive surface using a pipette and allowed to air dry. The electrolyte used in the experiment was a 0.5 M sodium sulfate solution. The photocurrent response was measured by periodically alternating between illumination and shading states. The EIS test parameters were set as follows: high frequency 100 kHz, low frequency 0.1 Hz, and amplitude 50 mV. Mott-Schottky curves were measured at 500 Hz, 750 Hz, and 1000 Hz on the electrochemical workstation to calculate the flat band potential of the material and the conduction band (CB) value. Current-voltage (IV) measurements were obtained by applying different voltages and test currents to the FTO and Au electrodes after magnetron sputtering of the CdS wafer.
[0025] Photocatalytic hydrogen evolution test: The photocatalytic activity of each sample was tested using the photocatalytic H2 evolution method. The reaction vessel adopted a top-illuminated design and was connected to a closed gas circulation system. Typically, 5 mg of photocatalyst powder was first dispersed in 30 mL of an aqueous solution containing 0.25 M sodium sulfite and 0.35 M sodium sulfide. After ultrasonic treatment for 5 minutes, the suspension was magnetically stirred during the photocatalytic test. A vacuum chamber was used to evacuate the reaction vessel to ensure a vacuum environment. Subsequently, the reaction was conducted under simulated solar spectrum (300 W xenon lamp, 200 mW / cm²). 2 The reaction was carried out using a 6°C circulating water cooling system. Hydrogen gas was detected by an Agilent GC-8860 gas chromatograph equipped with a thermal conductivity detector (TCD). Visible light testing was performed using a 420 nm cutoff filter to filter ultraviolet light. Cyclic stability testing was conducted every 2 hours. After each photocatalytic reaction cycle, the reactor was first purged with air, then evacuated to remove residual hydrogen before starting the next cycle. The reaction conditions were exactly the same as described above, and all hydrogen evolution rate data were based on at least three independent replicate experiments, reporting the mean ± standard deviation.
[0026] This invention employs the Thermo Scientific K-Alpha system for XPS measurements; a JEM-2100F field emission transmission electron microscope (FET) manufactured by NEC Corporation is used to observe the microstructure and elemental distribution of the samples; a Shimadzu 6100 XRD is used to verify the phase information of the materials; and the samples are irradiated with ultraviolet light of a certain energy using a UPS. The work function (Φ) of BTO and CdS samples is then measured using an ESCALAB QXi X-ray photoelectron spectrometer manufactured by Thermo Fisher Scientific.
[0027] DFT calculations were performed using the VASP software package, employing the Projected Added Plane Wave (PAW) method to describe the electron-ion interaction, with a cutoff energy set to 400 eV. Geometric optimization and calculations of electronic and optical properties were performed using the PBE functional. A 20 Å vacuum layer was incorporated into the vertical direction of the slab model, and the Brillouin zone was sampled only at the Γ-point. The energy convergence criterion for the self-consistent electronic iteration and the atomic residual force convergence criterion were both set to 10 eV. -4 eV and 0.01eV / Å.
[0028] Beneficial effects
[0029] This invention loads gold nanoparticles onto the surface of a barium titanate substrate, and simultaneously contacts cadmium sulfide material with both the gold nanoparticles and the barium titanate substrate. The gold nanoparticles, positioned between the barium titanate substrate and the cadmium sulfide material, act as an electron transport medium. Due to the high conductivity of gold, this structure can reduce the interfacial charge transport resistance, promote the cross-interfacial transport of photogenerated carriers from the cadmium sulfide side to the barium titanate side, and form Schottky contacts in some interfacial regions. This is expected to suppress the reverse flow of photogenerated electrons, achieve spatial separation of photogenerated electrons and holes, and improve the photocatalytic hydrogen evolution performance. This invention utilizes a chemical precipitation sequence of "first adsorbing cadmium ions, then adding sulfide ions" to preferentially nucleate and grow cadmium sulfide on the surface of gold nanoparticles. Benefiting from the strong affinity between Au and S, the cadmium sulfide layer is anchored to the gold nanoparticle surface via Au-S bonds, enhancing the contact tightness of the heterojunction interface. Experiments show that this preparation sequence has minimal impact on the hydrogen evolution performance due to the deposition order of the cadmium sulfide precursor. In contrast, the activity of the unmodified barium titanate / cadmium sulfide heterojunction drops sharply to 10% of that when preferentially adsorbing cadmium ions, demonstrating that gold modification effectively stabilizes the interface structure. Under simulated sunlight irradiation (using 0.25 M sodium sulfite and 0.35 M sodium sulfide as sacrificial agents), the hydrogen evolution rate of the photocatalyst of this invention reaches 9.97 mmol·g⁻¹. -1 ·h -1 The values are barium titanate / cadmium sulfide heterojunctions (5.23 mmol·g). -1 ·h -1 ) and original cadmium sulfide (0.95 mmol·g -1 ·h -1 The hydrogen evolution performance was 1.9 times and 10.5 times that of the original catalyst, respectively. Under visible light irradiation (λ≥420 nm), the hydrogen evolution performance was also significantly enhanced, and the hydrogen evolution performance of the photocatalyst remained basically stable in five consecutive cycle tests. In addition, the introduction of gold nanoparticles caused a red shift in the absorption edge, which enhanced the light-harvesting ability and visible light utilization efficiency. The ultraviolet-visible diffuse reflectance spectrum showed that the absorption intensity of the photocatalyst of the present invention was significantly improved in the visible light region compared with barium titanate / cadmium sulfide heterojunction. Attached Figure Description
[0030] Figure 1 Schematic diagram of the preparation process of barium titanate / gold / cadmium sulfide heterojunction photocatalyst;
[0031] Figure 2 (a) X-ray diffraction (XRD) patterns of BTO, Au, CdS and BTO / Au / CdS; (b, c) High-resolution transmission electron microscopy (HRTEM) images of BTO / Au / CdS; (d) Selected-region elemental distribution map of BTO / Au / CdS heterojunction.
[0032] Figure 3EDS energy dispersive spectroscopy and elemental quantitative analysis results of BTO / Au / CdS samples;
[0033] Figure 4 Barium titanate / gold / cadmium sulfide heterojunction photocatalyst and comparative samples: (a) Hydrogen evolution rate of each sample under simulated sunlight; (b) Hydrogen evolution rate of each sample under visible light (λ>420nm); (c) Effect of different preparation methods on hydrogen evolution performance; (d) Stability test of BTO / Au / CdS after five cycles.
[0034] Figure 5 (a) UV-Vis DRS; (b) Transient photocurrent (TPC) response curve; (c) Electrochemical impedance spectroscopy (EIS) Nyquist plot; (d) Zeta potential comparison; (e, f) Effect of deposition sequence on hydrogen evolution performance of BTO / CdS and BTO / Au / CdS;
[0035] Figure 6 (ac) Work function plots of CdS, Au, and BTO calculated by DFT; (d) Secondary electron cutoff edge of UPS; (e) High-resolution Ti 2p XPS spectrum; (f) High-resolution S 2p XPS spectrum; (g) Electron paramagnetic resonance (EPR) spectrum; (h) IV characteristic curves of CdS / Au Schottky junction; (i) IV curves on logarithmic coordinates;
[0036] Figure 7 (a) Tauc curves of CdS and BTO; (b, c) Mott-Schottky curves of CdS and BTO; (d) Schematic diagram of redox potentials; (e) H2O2 yield of each sample under illumination; (f) Schematic diagram of band arrangement of CdS, Au and BTO before contact; (g) Schematic diagram of photocatalytic mechanism of BTO / Au / CdS. Detailed Implementation
[0037] The present invention will be described in detail below with reference to embodiments to enable those skilled in the art to better understand the present invention, but the present invention is not limited to the following embodiments. Unless otherwise specified, the raw materials and equipment involved in the embodiments are all conventional commercially available products in the art.
[0038] Example 1
[0039] Preparation of barium titanate substrate
[0040] 18.75 mmol (5.915 g) of barium hydroxide octahydrate was added to a 25 mL mixed solvent consisting of 10 mL of deionized water and 15 mL of anhydrous ethanol. The mixture was stirred and heated at 80 °C until completely dissolved. Then, 12.5 mmol (4.25 mL) of tetrabutyl titanate and 2 mL of ammonia were added, maintaining an atomic ratio of barium to titanium of 1.5. The mixture was stirred for another 30 min to obtain the precursor solution. The precursor solution was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, sealed, and subjected to hydrothermal reaction at 200 °C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was then removed and washed five times alternately with deionized water and anhydrous ethanol, and dried at 60 °C for 24 h to obtain the barium titanate substrate.
[0041] like Figure 2 As shown in (a), XRD characterization revealed that the product was barium titanate in the perovskite phase, and the characteristic peaks matched well with the standard card PDF#04-007-9931.
[0042] Example 2
[0043] Preparation of barium titanate / gold composite
[0044] 500 mg of barium titanate substrate was ultrasonically dispersed in 80 mL of deionized water. 2 mL of ammonia and 3 mL of tetrachloroauric acid solution (5 mg / mL) were added, and the mixture was reacted at 80 °C for 1 h to deposit the gold precursor onto the barium titanate surface. The product was then centrifuged, washed, dried, and heat-treated at 400 °C for 2 h in an inert atmosphere to reduce the gold precursor to metallic gold nanoparticles, with a theoretical gold mass loading of 1.7%. The resulting product was centrifuged for 3 min to achieve solid-liquid separation, washed three times with deionized water and once with anhydrous ethanol, and dried at 60 °C for 24 h. The dried product was then sealed and stored for later use.
[0045] EDS elemental analysis showed that the actual mass loading of gold nanoparticles in the barium titanate / gold composite obtained in this example was 0.8% (the theoretical feed amount was 1.7%), indicating that tetrachloroauric acid was successfully reduced and deposited. TEM observation showed that the gold nanoparticles were uniformly dispersed on the surface of the barium titanate substrate, with a particle size distribution of 3–7 nm and an average particle size of about 5 nm.
[0046] Example 3
[0047] The barium titanate / gold / cadmium sulfide heterojunction photocatalyst was prepared by a two-step chemical deposition process: first, gold nanoparticles were deposited on the surface of a barium titanate substrate by a deposition-precipitation method combined with thermal reduction, and then a cadmium sulfide layer was deposited on the surface of the barium titanate / gold composite by chemical precipitation.
[0048] Specifically, 100 mg of the barium titanate / gold composite obtained in Example 2 was added to 60 mL of deionized water and ultrasonically dispersed in an ultrasonic cleaner for 30 min to form a stable suspension. 215 μL of a 0.2 mol / L cadmium acetate dihydrate solution was slowly added under magnetic stirring. After mixing until homogeneous, the mixture was placed in a light-protected environment for 30 min to allow cadmium ions to be fully adsorbed onto the surface of the barium titanate / gold composite. Subsequently, 430 μL of a freshly prepared 0.1 mol / L sodium sulfide solution was slowly added dropwise under continuous stirring. After the addition was complete, the reaction continued for 30 min, resulting in the chemical precipitation of a cadmium sulfide layer on the surface of the barium titanate / gold composite, yielding a barium titanate / gold / cadmium sulfide heterojunction photocatalyst. The obtained product was centrifuged for 3 min to achieve solid-liquid separation, washed three times with deionized water and once with anhydrous ethanol, dried at 60 °C for 24 h, and then sealed for storage. The amount of cadmium acetate dihydrate added was 0.043 mmol, and the theoretical production of CdS was about 6.21 mg. The mass ratio of CdS to BTO / Au relative to 100 mg of BTO / Au complex was about 0.062:1.
[0049] See Figure 2 (b) and (c) HRTEM showed that cadmium sulfide nanoparticles were tightly anchored on the surface of gold nanoparticles and in direct contact with the barium titanate substrate, i.e., CdS was tightly anchored on the Au surface and in contact with BTO, forming a three-phase contact interface. Figure 2 The elemental distribution diagram (d) confirms the uniform distribution of Ba, Ti, O, Au, Cd, and S elements in the heterojunction region.
[0050] Example 4
[0051] Preparation of barium titanate / gold / cadmium sulfide heterojunction photocatalysts with different gold loadings
[0052] Following the preparation methods of Examples 2 and 3, only the amount of tetrachloroauric acid solution added in step S2 was changed (using 0.5 mL, 1 mL, 2 mL, 4 mL, and 6 mL of 5 mg / mL HAuCl4 solution, respectively), to prepare barium titanate / gold / cadmium sulfide heterojunction photocatalysts with different gold loadings. EDS analysis determined the actual gold loadings to be 0.2%–0.3%, 0.5%–0.7%, 1.0%–1.2%, 2.1%–2.4%, and 3.0%–3.5%, respectively. Photocatalytic hydrogen evolution tests showed that the actual gold loading range of 0.3%–5% consistently yielded superior hydrogen evolution performance compared to the barium titanate / cadmium sulfide heterojunction, with the best performance observed in the range of 0.8%–2.5%.
[0053] Comparative Example 1
[0054] Preparation of barium titanate / cadmium sulfide heterojunction
[0055] Except for replacing the barium titanate / gold composite in Example 3 with 100 mg barium titanate substrate (product of Example 1, unloaded with gold), the remaining steps were the same as in Example 3 to obtain a barium titanate / cadmium sulfide heterojunction.
[0056] Comparative Example 2
[0057] Preparation of virgin cadmium sulfide
[0058] Dissolve an appropriate amount of cadmium acetate dihydrate in deionized water to prepare 15 mL of a 0.2 mol / L cadmium acetate dihydrate solution. Under magnetic stirring, slowly and uniformly add 30 mL of freshly prepared 0.1 mol / L sodium sulfide solution. After the addition is complete, continue the reaction for 30 min. Centrifuge the resulting yellow product for 3 min to achieve solid-liquid separation. Wash the product three times with deionized water and once with anhydrous ethanol. Dry the product at 60℃ for 24 h to obtain the cadmium sulfide sample.
[0059] Comparative Example 3
[0060] Physically mixed samples
[0061] The barium titanate / gold composite obtained in Example 2 and the cadmium sulfide obtained in Comparative Example 2 were simply ground and mixed in a mortar at a feeding ratio equivalent to that in Example 3 (barium titanate / gold composite:cadmium sulfide mass ratio ≈ 1:0.062) without chemical deposition to obtain a simple powder mixture. Separately, the barium titanate / gold composite and cadmium sulfide at the same feeding ratio were magnetically stirred and mixed in deionized water for 4 h, followed by centrifugation and drying to obtain a physically stirred mixed sample. Figure 4 As shown in (c), the activity of physically ground and physically stirred mixed samples was 0.48 and 2.48 mmol·g, respectively. -1 ·h -1 The concentrations were significantly lower than those of chemically deposited samples (9.97 mmol·g). -1 ·h -1 This demonstrates that interfacial chemical contact is key to performance improvement.
[0062] Comparative Example 4
[0063] Barium titanate / cadmium sulfide and barium titanate / gold / cadmium sulfide samples with different deposition sequences
[0064] Following the preparation methods of Comparative Example 1 and Example 3, only the order of adding the precursor in step S3 was changed: first, sodium sulfide solution was added for adsorption for 20-60 min, and then cadmium acetate dihydrate solution was added for reaction for 20-60 min (i.e., adsorption of S was performed first). 2- Post-adsorption of Cd 2+ Barium titanate / cadmium sulfide samples and barium titanate / gold / cadmium sulfide samples with different deposition sequences were prepared.
[0065] Photocatalytic hydrogen evolution test method:
[0066] The experiment was carried out in 30 mL of an aqueous solution containing 0.25 M Na₂SO₃ and 0.35 M Na₂S, with a catalyst dosage of 5 mg and a 300 W xenon lamp (200 mW / cm²). 2 The hydrogen production was determined by gas chromatography (TCD detector) with 6℃ circulating water cooling. Photoelectric performance was assessed using a CHI-660 electrochemical workstation with 0.5M Na2SO4 as the electrolyte. The working electrode was prepared using the FTO coating method.
[0067] In the accompanying drawings of the instruction manual:
[0068] Figure 1 Schematic diagram of the preparation process of barium titanate / gold / cadmium sulfide heterojunction photocatalyst;
[0069] Figure 2 (a) X-ray diffraction (XRD) patterns of BTO, Au, CdS and BTO / Au / CdS; (b, c) High-resolution transmission electron microscopy (HRTEM) images of BTO / Au / CdS; (d) High-angle annular dark-field (HAADF) elemental distribution images of Ba, Ti, O, Au, Cd and S elements in selected regions of the BTO / Au / CdS heterojunction.
[0070] Figure 3 The EDS energy dispersive spectroscopy and elemental mass percentage quantitative results of the BTO / Au / CdS samples show that the mass percentage of Au in BTO / Au / CdS is approximately 0.8%.
[0071] Figure 4 The bar graphs (a) showing the hydrogen evolution rate of the barium titanate / gold / cadmium sulfide heterojunction photocatalyst and the control sample (3a) under simulated sunlight (300 W xenon lamp, no filter) are used to plot the hydrogen evolution rate of each sample. The horizontal axis is labeled with pure BTO, pure CdS, BTO / CdS, and BTO / Au / CdS, and the vertical axis is the H2 yield (mmol·g). -1 ·h -1The data shows that the ratio of pure BTO is only 0.13, and that of pure CdS is 0.95, with the BTO / CdS ratio significantly increasing to 5.23. The BTO / Au / CdS ratio reaches a maximum of 9.97, which is 1.9 times and 10.5 times that of BTO / CdS and CdS, respectively. (b) is a bar chart of hydrogen evolution rate of each sample under visible light (λ>420 nm) irradiation. (c) shows the effect of different preparation methods on hydrogen evolution performance. The BTO / Au / CdS samples obtained by physical grinding and mixing, physical stirring and mixing, and chemical deposition were compared. The bar chart shows that the activity of the chemically deposited sample (9.97) is much higher than that of the physically mixed sample (0.48 and 2.48), proving the key role of interfacial chemical contact. (d) Five-cycle stability test of BTO / Au / CdS, with the horizontal axis representing the number of cycles and the vertical axis representing H2 production (mmol·g). -1 ·h -1 The results showed that the activity remained essentially unchanged after five consecutive cycles, with no significant attenuation.
[0072] Figure 5 (a) is the UV-Vis DRS, with wavelength (nm) on the x-axis and absorbance (au) on the y-axis. The curve shows that BTO / Au / CdS has significantly enhanced absorption intensity in the visible region (>400 nm) and a red shift in the absorption edge compared to BTO / CdS; (b) is the transient photocurrent (TPC) response curve, with time (s) on the x-axis and photocurrent density (μA / cm²) on the y-axis. 2 (a) Under periodic illumination switching, BTO / Au / CdS has the highest photocurrent density, followed by BTO / CdS, while pure CdS and BTO have the lowest. (c) is the Nyquist plot of electrochemical impedance spectroscopy (EIS), with the horizontal axis representing Z' (real part) and the vertical axis representing -Z'' (imaginary part). BTO / Au / CdS has a smaller real intercept and lower interfacial charge transfer resistance. (d) is the Zeta potential histogram, comparing BTO (-2.66 mV) and BTO / Au (+2.06 mV), showing that Au modification changes the surface potential from negative to positive. (e) and (f) are the effects of deposition order on the hydrogen evolution performance of BTO / CdS and BTO / Au / CdS, respectively. The horizontal axis represents the order of addition of different precursors (CdS first, then Au). 2+ After S 2- vs First S 2- After Cd 2+ The vertical axis represents the yield, and the ratio of BTO / CdS preferentially adsorbs S. 2- The activity drops sharply to preferential adsorption of Cd. 2+ The performance of BTO / Au / CdS remained stable in both sequences, while the performance of BTO / Au / CdS was approximately 10% lower.
[0073] Figure 6Figures (a), (b), and (c) show the work functions calculated by density functional theory (DFT), providing the values for CdS (5.49 eV), Au (5.16 eV), and BTO (4.93 eV), respectively, satisfying the trend Φ(CdS)>Φ(Au)>Φ(BTO). Figure (d) shows the secondary electron cutoff edge of ultraviolet photoelectron spectroscopy (UPS), with measured work functions of 5.54 eV and 4.43 eV for CdS and BTO, respectively, consistent with DFT. Figure (e) shows the high-resolution Ti 2p XPS spectrum, comparing BTO and BTO / Au; the latter shows a positive shift in the Ti 2p binding energy, indicating electron transfer from BTO to Au. Figure (f) shows the high-resolution S 2p XPS spectrum, comparing CdS and CdS / Au; the latter shows a positive shift in the S 2p binding energy. (g) shows the positive shift of the 2p binding energy; (h) shows the electron paramagnetic resonance (EPR) spectrum, which indicates the presence of defect signals in BTO / Au / CdS, attributed to the Fermi level pinning effect induced by surface defects; (h) shows the current-voltage (IV) characteristic curve of the CdS / Au Schottky junction, which exhibits a nonlinear response; (i) shows the IV curve on logarithmic coordinates, further analyzing the conduction mechanism.
[0074] Figure 7 (a) shows the Tauc curves (αhν) of CdS and BTO. 2 (v vs hν), extrapolated, the band gap of CdS is 2.21 eV, and the band gap of BTO is 3.31 eV; (b) and (c) are the Mott-Schottky curves of CdS and BTO, respectively (1 / C 2 The slopes of both are positive, indicating that they are both n-type semiconductors. The flat band potentials (Ag / AgCl, pH=7) are -1.10 V and -0.66 V, respectively. Considering that the flat band potential is about 0.1 eV negative than the conduction band potential, they are converted to RHE as -0.49 V and -0.05 V; (d) is a schematic diagram of each redox potential, with O2 / H2O2 (-0.33 V vs RHE) and O2 / •O2 marked. - (-0.33 V) isoelectric potential, compared with the conduction band positions of CdS and BTO; (e) is a bar chart of H2O2 yield for each sample (CdS, BTO, BTO / CdS, BTO / Au / CdS) under illumination, with CdS yield approximately 166.5 μmol·g. -1 ·h -1The sample containing BTO had almost zero electrons, indicating that the conduction band electrons of CdS had already been transferred to BTO before participating in the reduction; (f) is a schematic diagram of the band arrangement of CdS, Au and BTO before contact, with their respective work functions and band edge positions marked, showing the Fermi level difference; (g) is a schematic diagram of the photocatalytic mechanism of BTO / Au / CdS, showing that under illumination, CdS generates electron-hole pairs, and electrons are rapidly transferred to BTO through the Au transport bridge. At the same time, the double Schottky barrier inhibits electron backflow, and the holes remain in CdS to participate in the oxidation reaction, thereby achieving efficient spatial separation.
[0075] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A barium titanate / gold / cadmium sulfide heterojunction photocatalyst, characterized in that: The invention comprises a perovskite-phase barium titanate substrate, gold nanoparticles loaded on the surface of the barium titanate substrate, and a cadmium sulfide nanoparticle layer; wherein the average particle size of the gold nanoparticles is 3-7 nm; the cadmium sulfide nanoparticle layer at least partially covers the surface of the gold nanoparticles and forms a three-phase contact interface with the gold nanoparticles and the barium titanate substrate in at least a partial region; the gold nanoparticles are located between the barium titanate substrate and the cadmium sulfide nanoparticle layer, serving as an electron transport medium between the barium titanate substrate and the cadmium sulfide nanoparticle layer.
2. The barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 1, characterized in that: Schottky contacts are formed between the gold nanoparticles and the barium titanate substrate, and between the gold nanoparticles and the cadmium sulfide nanoparticle layer, respectively, constituting a double Schottky barrier structure.
3. The barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 1, characterized in that: The barium titanate substrate is a perovskite phase barium titanate.
4. The barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 1, characterized in that: The cadmium sulfide material is a cadmium sulfide nanoparticle layer, which at least partially covers the surface of the gold nanoparticles and is connected to the barium titanate substrate through the gold nanoparticles; at the same time, the cadmium sulfide material also covers at least a portion of the barium titanate substrate that is not loaded with gold nanoparticles and is in direct contact with the barium titanate substrate.
5. The barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 1, characterized in that: The average particle size of the gold nanoparticles is 5 nm; the actual mass loading of the gold nanoparticles is 0.2-3.5%, preferably 1.6-1.8%; the mass ratio of cadmium sulfide to barium titanate substrate in the cadmium sulfide material is 0.05-0.3:1, preferably 0.062:
1.
6. A method for preparing a barium titanate / gold / cadmium sulfide heterojunction photocatalyst as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of barium titanate substrate; S2. Depositing gold nanoparticles on the surface of a barium titanate substrate: The barium titanate substrate is dispersed in water, tetrachloroauric acid solution and ammonia are added, and the reaction is carried out at 70-90°C for 0.5-2 hours. Gold nanoparticles are deposited on the surface of the barium titanate substrate by a deposition-precipitation method to obtain a barium titanate / gold composite. S3. A cadmium sulfide layer is deposited on the surface of a barium titanate / gold composite by chemical precipitation to obtain a barium titanate / gold / cadmium sulfide heterojunction photocatalyst. In this process, the barium titanate / gold composite is first dispersed in a precursor solution containing cadmium ions, so that the cadmium ions are adsorbed on the surface of the barium titanate / gold composite, and then a precursor solution containing sulfur ions is added to carry out the reaction.
7. The method for preparing the barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 6, characterized in that: In step S1, when preparing the barium titanate substrate, barium hydroxide octahydrate and tetrabutyl titanate are dispersed in a mixed solvent of water and ethanol at a molar ratio of 1.2 to 2:1, ammonia is added, and the mixture is hydrothermally reacted at 180 to 220°C for 18 to 30 hours to obtain the barium titanate substrate.
8. The method for preparing the barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 6, characterized in that: In step S2, the amount of tetrachloroauric acid added is calculated based on the theoretical mass loading of gold of 0.5% to 5%. The gold nanoparticles are obtained by reduction treatment through a deposition-precipitation method, specifically including: dispersing the barium titanate substrate in water, adding tetrachloroauric acid solution and ammonia, stirring and reacting at 70 to 90 °C for 0.5 to 2 h to deposit the gold precursor on the surface of barium titanate, followed by centrifugation, washing, drying, and heat treatment at 300 to 500 °C for 1 to 3 h in an inert atmosphere to reduce the gold precursor to metallic gold nanoparticles, thus obtaining the barium titanate / gold composite.
9. The method for preparing the barium titanate / gold / cadmium sulfide heterojunction photocatalyst according to claim 6, characterized in that: In step S3, the barium titanate / gold composite is dispersed in water, cadmium acetate dihydrate solution is added, and the mixture is stirred and adsorbed for 20-60 minutes. Then, sodium sulfide solution is added and reacted for 20-60 minutes to form cadmium sulfide material by chemical precipitation. The cadmium ion adsorption process is carried out under light-protected conditions. The molar ratio of cadmium acetate dihydrate to sodium sulfide is 1:
1.
10. The application of a barium titanate / gold / cadmium sulfide heterojunction photocatalyst as described in any one of claims 1-5 or a barium titanate / gold / cadmium sulfide heterojunction photocatalyst prepared by the preparation method as described in any one of claims 6-9 in photocatalytic water splitting for hydrogen production.
Citation Information
Patent Citations
BaTiO3-CdS nanometer composite photocatalyst and preparation method thereof
CN107670672A